Ultrasound evaluation of movement of each hemidiaphragm in the postoperative period of upper abdomen surgery: Effect of previous intercostal block with local anesthetics - Monti, José; Riva, Juan; Nieto, Fernando; Piriz, Héctor (Cirugía del Uruguay, 2001)
Premise: Diaphragmatic dysfunction appears to be a majar determinant in the onset of respiratory complications during the postoperative period (PO) of upper adominal surgery. Objective: To evaluate by means of ultrasound any changes in diaphragmatic movements brought on by open cho/ecystectomy and the effect on such changes of intercostal infiltration with Bupivacaine, prior to incision.